Mentha arvensis Essential Oil Exerts Anti-Inflammatory in LPS-Stimulated Inflammatory Responses via Inhibition of ERK/NF-κB Signaling Pathway and Anti-Atopic Dermatitis-like Effects in 2,4-Dinitrochlorobezene-Induced BALB/c Mice - So-Yeon Kim; Sang-Deok Han; Minju Kim; Tamanna Jahan Mony; Eun-Seok Lee; Kyeong-Min Kim; Seung-Hyuk Choi; Sun Hee Hong; Ji Woong Choi; Se Jin Park (Antioxidants, 2021)
The mechanism of atopic dermatitis (AD) is modulated by the release of cytokines and chemokines through the mitogen-activated protein kinase (MAPK)/nuclear factor-kappa B (NF-κB) signaling pathway. Topical steroids are used to treat AD, but some people need safer anti-inflammatory drugs to avoid side effects. Mentha arvensis has been used as a herbal plant with medicinal properties, but its anti-inflammatory effects have not been elucidated in an AD model. In this study, we investigated the anti-inflammatory effects of M. arvensis essential oil (MAEO) and its underlying molecular mechanism in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages and HaCaT cells (human epidermal keratinocyte). Additionally, we examined the ameliorating effects of the MAEO in a dinitrochlorobenzene (DNCB)-induced murine model of AD. We found, in both RAW 264.7 cells and HaCaT cells, MAEO inhibited LPS-stimulated inflammatory mediators such as nitric oxide (NO) and prostaglandin E2 and proinflammatory cytokines, including IL-1β and IL-6, due to the suppression of COX-2 and iNOS expression. In LPS-stimulated macrophages, we also observed that MAEO inhibited the phosphorylation of ERK and P65. Furthermore, MAEO treatment attenuated AD symptoms, including the dermatitis score, ear thickness, epidermal thickness and infiltration of mast cells, in a DNCB-induced animal model of AD. Overall, our findings suggest that MAEO exerts anti-inflammatory and anti-atopic dermatitis effects via inhibition of the ERK/NF-κB signaling pathway.